COVID-19 AS A LINGUISTIC PHENOMENON AND ITS INFLUENCE ON THE DEVELOPMENT OF MODERN REGIONAL TERMINOLOGY (Journal of Pharmaceutical Negative Results, 2022)
The article is devoted to the study of COVID-19 as a linguistic phenomenon based on the material of the Russian and English languages, as well as the impact of the pandemic on the vocabulary of two languages. The article examines the influence of the course of the coronavirus pandemic on the meaning of neologisms of lexico-semantic field “COVID-19”. The beginning of 2020 was marked by the coronavirus epidemic, which turned into a pandemic. The wide spread of the disease affected not only the functioning of medicine and other social institutions, but also the lexical composition of languages, in particular English and Russian. At a time of social upheaval, the processes of language development are accelerating, an impression of chaos and instability is created. Among the most popular ways of forming coronovirus terms are metaphor, word formation (prefix and suffix methods), composition, truncation and abbreviation. In Russian, there is an active borrowing of the corresponding terms from the English language. The main research methods are component analysis of dictionary definitions. In addition, a semantic analysis is carried out on the basis of introspection and the use of linguistic observation and a descriptive method. In accordance with the peculiarities of the situation in society, the psychological attitudes of the masses, their linguistic taste and flair of the language are changing. A comprehensive linguistic analysis of the research material made it possible to establish that the lexeme COVID-19 in the English mass media discourse acquires additional connotations and serves to form an informational picture of the world that reflects the national-cultural characteristics of worldview and the system of axiological relations.